Use of business planning methods to monitor global health budgets in Turkmenistan - Tim Ensor; Bakhtigul Amannyazova (Bulletin of the World Health Organization, 2000)
After undergoing many changes, the financing of health care in countries of the former Soviet Union is now showing signs of maturing. Soon after the political transition in these countries, the development of insurance systems and fee-for-service payment systems dominated the discussions on health reform. At present there is increasing emphasis on case mix adjusted payments in larger hospitals and on global budgets in smaller district hospitals. The problem is that such systems are often mistrusted for not providing sufficient financial control. At the same time, unless further planned restructuring is introduced, payment systems cannot on their own induce the fundamental change required in the health care system. As described in this article, in Tejen etrap (district), Turkmenistan, prospective business plans, which link planned objectives and activities with financial allocations, provide a framework for setting and monitoring budget expenditure. Plans can be linked to the overall objectives of the restructuring system and can be used to ensure sound financial management. The process of business planning, which calls for a major change in the way health facilities examine their activities, can be used as a vehicle to increase awareness of management issues. It also provides a way of satisfying the requirement for a rigorous, bottom-up planning of financial resources.